Perceived coercion amongst healthcare workers during the COVID-19 pandemic - Andrea S. Stoltenberg; Veronica Ranieri; Hege Kristine N. Dahlen; Eleni Nastouli; SAFER Investigators; Roger Almvik; Sarah J. L. Edwards; Sunjeev K. Kamboj (Scientific Reports)
Abstract Direct and prolonged exposure to stress and uncertainty among healthcare workers (HCWs) during the COVID-19 pandemic likely had a significant negative impact on their mental health and general wellbeing. Although the contributors to such distress remain to be fully understood, the construct of perceived coercion appears to be relevant. Among HCWs, perceived coercion is conceptualised as appraisals about lack of control/‘freedom to choose’ and pressure to perform patient-care duties in the context of unprecedented threat of contagion from patients. To improve our understanding of perceived coercion amongst HCWs, we developed a 10-item scale—the Pandemic-specific Perceived Coercion Scale for Healthcare Workers (PPCS-HCW) scale—designed to be adaptable and applicable for use in future mass-contagion emergencies. A preliminary (exploratory) factor analysis (N = 546) showed that relevant items coalesced around three factors—‘internal pressure’, ‘external pressure’ and ‘perceived coercion’, that partly overlap with previous conceptualisations of perceived coercion. The exploratory conceptual and psychometric structure was confirmed in a separate sample of HCWs from the UK and Norway (N = 483). On average, across the three PPCS-HCW scale factors, HCWs showed low levels of perceived coercion (M = 0.22 (95% CI [0.11, 0.33] on a − 3 to + 3 scale). However, cluster analysis identified three groups: low (− 1.09 (95% CI [− 1.20, − 0.99]), moderate (0.17 (95% CI [0.08, 0.25]) and high scoring (1.57 (95% CI [1.47, 1.67]) PPCS-HCW clusters. High scoring participants showed higher levels of psychological distress, avoidance coping and compassion fatigue. In summary, our findings suggest that perceived coercion is a relevant construct in understanding the adverse psychological impact of large-scale contagion emergencies on HCWs.